The Cephenniini of China. VI. New species and new records of Cephennodes Reitter from Hainan, Guangxi and Guangdong (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Five new Chinese species of Cephennodes (s. str.) are described: C. bicavatus sp. n. (Guangdong), C. pseudobos sp. n. (Guangxi), C. huapingensis sp. n. (Guangxi), C. elevatus sp. n. (Guangxi), and C. gaozhaianus sp. n. (Guangxi). Cephennodes qiongdaoanus Jałoszyński and C. capricornis Jałoszyński are recorded for new localities in the provinces of Guangxi and Hainan, respectively. Diagnostic characters of all hitherto known representatives of the Cephennodes taurus, Cephennodes bos and Cephennodes impressifrons species groups are compiled.